Should I scan my face? The influence of perceived value and trust on Chinese users' intention to use facial recognition payment - Bo Hu; Yu-li Liu; Wenjia Yan (International Telecommunications Society (ITS), 2021)
Drawing on the perspectives of perceived value and trust, this study examines the factors affecting Chinese users' intention to use facial recognition payment (FRP) service. Data collected from 1200 Chinese mobile payment users is analyzed by using structural equation modelling. Results show that convenience positively influences perceived value; privacy risk and financial risk negatively influence perceived value. Only privacy risk and financial risk can significantly affect trust in FRP. Novelty has no significant effect on perceived value and trust. It is also found that perceived value positively influences trust, and both perceived value and trust are factors positively affecting intention to use FRP. Information sensitivity moderates the relationship between perceived value and intention to use FRP. Theoretical implications and practical implications are discussed.
Keywords: 330; facial recognition payment; perceived value; trust; intention to use